Whole genome sequences of nine Taylorella equigenitalis strains isolated in the Czech Republic between 1982–2021: Molecular dating suggests a common ancestor at the time of Roman Empire - Matěj Hrala; Petr Andrla; Juraj Bosák; Pavla Fedrová; Amir Mugutdinov; Renata Karpíšková; Kateřina Nedbalcová; Jitka Raichová; Martin Faldyna; Petr Hořín; David Šmajs (PLoS ONE, 2025)
Taylorella equigenitalis is the causative agent of sexually transmitted contagious equine metritis. Infections manifest as cervicitis, vaginitis and endometritis and cause temporary infertility and miscarriages of mares. While previous studies have analyzed this organism for various parameters, the evolutionary dynamics of this pathogen, including the emergence of antibiotic resistance, remains unresolved. The aim of this study was to isolate contemporary strains, determine their genome sequences, evaluate their antibiotic resistance and compare them with other strains. We determined nine complete whole genome sequences of T. equigenitalis strains, mainly from samples collected from Kladruber horses in the Czech Republic. While T. equigenitalis strains from Kladruby isolated between 1982 and 2018 were inhibited by streptomycin, contemporary strains were found to be resistant to streptomycin, suggesting the recent emergence of this mutation. In addition, we used the collection dates of Kladruber horse strains to estimate the genome substitution rate, which resulted in a scaled mean evolutionary rate of 6.9×10−7 substitutions per site per year. Analysis with other available T. equigenitalis genome sequences (n = 18) revealed similarity of the Czech T. equigenitalis genomes with the Austrian T. equigenitalis genome, and molecular dating suggested a common ancestor of all analyzed T. equigenitalis strains from 1.5–2.6 thousand years ago, dating to the first centuries A.D. Our study revealed a recently emerged streptomycin resistance in T. equigenitalis strains from Kladruber horses, emphasizing the need for antibiotic surveillance and alternative treatments. Additionally, our findings provided insights into the pathogen’s evolution rate, which is important for understanding its evolution and preparing preventive strategies.